HUBUNGAN PENYULUHAN KESEHATAN DENGAN TINGKAT PENGETAHUAN DAN PERILAKU TERHADAP PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA SISWI KELAS 3 MADRASAH TSANAWIYAH NEGERI 1 PADANG LAWAS TAHUN 2019 - SYAKINAH AMILINA SIREGAR; SITI MIRHALINA (LP2MTBM MAKARIOZ, 2021)
Breast cancer is one of frightening cancer for women around the world. It is mostly found at a young age, there are even girlsaged fourteen having tumors in their breasts that can potentially become cancerous if not detected early.SADARI (Self Breast Examination) is an examination for woman to detect breast cancer by looking for lumps orabnormalities in breast itself. Health education as primary and secondary prevention efforts in breast cancer has animportant role to increasing people knowledge. This study aims to determine the relationship of health education withknowledge and behavior level towards breast self examination in grade 3 Madrasah Tsanawiyah Negeri 1 Padang Lawasstudents in 2019. This research type is experimental with pre-experiment design and one pretest-posttest design group type.The research sample was obtained using total sampling technique totaling 120 grade 3 students that inclusion criteria.Data analysis using Wilcoxon analysis. Knowledge and behavior level of female students was significantly different beforeand after counseling with p = 0,000 (p <0.05). A relationship was found between counseling and the knowledge andbehavior level.